Draft Genome Sequence of Lactobacillus jensenii UMB0847, Isolated from the Female Urinary Tract - West-Pelak, Ella (Microbiol Resour Announc, 2020)
Lactobacillus jensenii is a protective bacterium native to the female urinary tract. Here, we present the 1.6-Mbp draft genome for Lactobacillus jensenii UMB0847, isolated from a catheterized urine sample obtained from a pregnant female.